Prognostic significance of postsurgery circulating tumor DNA in nonmetastatic colorectal cancer: Individual patient pooled analysis of three cohort studies. Issue 4 (6th October 2020) - Tie, Jeanne; Cohen, Joshua D.; Lo, Serigne N.; Wang, Yuxuan; Li, Lu; Christie, Michael; Lee, Margaret; Wong, Rachel; Kosmider, Suzanne; Skinner, Iain; Wong, Hui Li; Lee, Belinda; et al.
Abstract: Studies in multiple solid tumor types have demonstrated the prognostic significance of ctDNA analysis after curative intent surgery. A combined analysis of data across completed studies could further our understanding of circulating tumor DNA (ctDNA) as a prognostic marker and inform future trial design. We combined individual patient data from three independent cohort studies of nonmetastatic colorectal cancer (CRC). Plasma samples were collected 4 to 10 weeks after surgery. Mutations in ctDNA were assayed using a massively parallel sequencing technique called SafeSeqS. We analyzed 485 CRC patients (230 Stage II colon, 96 Stage III colon, and 159 locally advanced rectum). ctDNA was detected after surgery in 59 (12%) patients overall (11.0%, 12.5% and 13.8% for samples taken at 4‐6, 6‐8 and 8‐10 weeks; P = .740). ctDNA detection was associated with poorer 5‐year recurrence‐free (38.6% vs 85.5%; P  < .001) and overall survival (64.6% vs 89.4%; P  < .001). The predictive accuracy of postsurgery ctDNA for recurrence was higher than that of individual clinicopathologic risk features. Recurrence risk increased exponentially with increasing ctDNA mutant allele frequency (MAF) (hazard ratio, 1.2, 2.5 and 5.8 for MAF of 0.1%, 0.5% and 1%). Postsurgery ctDNA was detected in 3 of 20 (15%) patients with locoregional and 27 of 60 (45%) with distant recurrence ( P = .018). This analysis demonstrates a consistent long‐term impact of ctDNA as a prognostic marker across nonmetastatic CRC, where ctDNA outperforms other clinicopathologic risk factors and MAF further stratifies recurrence risk. ctDNA is a better predictor of distant vs locoregional recurrence. Abstract : What's new? Pathology‐based cancer staging, by which a patient is classified as high‐risk or low‐risk, cannot perfectly predict which patients will experience a recurrence. Circulating tumor DNA (ctDNA) analysis can more accurately predict recurrence than clinico‐pathologic features. Here, the authors report a combined analysis of three independent cohort studies of patients with non‐metastatic colorectal cancer (CRC). Patients with detectable ctDNA after surgery had a significantly lower 5‐year survival rate. The ctDNA was sequenced to detect mutations, and recurrence risk increased exponentially with increasing mutant allele fraction of ctDNA.